Anti-ferroelectric film and preparation method thereof, and anti-ferroelectric capacitor containing same and preparation method thereof
By adding ABO3 paraelectric precursor to the antiferroelectric material PbZrO3, a multi-layer paraelectric-antiferroelectric structure is constructed, which solves the problems of low antiferroelectric-ferroelectric transformation field and large hysteresis, and achieves high energy storage density and efficiency and optimize the preparation process through anti-lead loss layer and sintering aid.
Patent Information
- Application Number
- CN202411804917.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-12-10
AI Technical Summary
The existing antiferroelectric material PbZrO3 has problems with low antiferroelectric-ferroelectric transformation field, large hysteresis, and limited energy storage density.
By mixing PbZrO3 with ABO3 paraelectric precursor solution, a thin film with multi-layer paraelectric-antiferelectric structure is prepared, and the polarization discontinuous construction of the antiferroelectric-paraelectric interface is used to delay the transition field and reduce hysteresis, thereby improving the Energy storage density and efficiency.
The delayed transition field is achieved, reducing hysteresis, improving energy storage density and efficiency, and reducing the pyrolysis temperature through anti-lead loss layer and sintering aid, improving the simplicity of the preparation method.
Smart Images

Figure CN119287350A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electronic materials, and in particular to an antiferroelectric film and a preparation method thereof, an antiferroelectric capacitor containing the same and a preparation method thereof. Background Art
[0002] Antiferroelectric capacitors are capacitors that use antiferroelectric materials. Antiferroelectric materials have a special antiparallel polarization configuration. This configuration exhibits paraelectric characteristics under low fields, and is induced to a ferroelectric phase under high fields, resulting in a field-induced antiferroelectric-ferroelectric phase transition. Therefore, polarization saturation can be effectively delayed, and they have good energy storage prospects. At the same time, antiferroelectric materials also have the advantages of fast polarization switching speed and wide operating temperature range. They are expected to be used in complex environments and working conditions, and have very high power density. The current mainstream antiferroelectric material is PbZrO3, but it has disadvantages such as low antiferroelectric-ferroelectric transition field and large hysteresis, which limits the energy storage density of antiferroelectric capacitors.
[0003] In order to solve the above problems existing in the prior art, the present invention is provided. Summary of the invention
[0004] The invention aims to solve the technical problems in the prior art of using PbZrO3 as the antiferroelectric material, such as low antiferroelectric-ferroelectric transition field, large hysteresis, limited energy storage density, etc. The invention provides an antiferroelectric film and a preparation method, an antiferroelectric capacitor containing the same and a preparation method. The antiferroelectric film has a frustrating effect, which can improve the stability of the antiferroelectric phase, delay the antiferroelectric-ferroelectric transition field and reduce the hysteresis of the hysteresis loop.
[0005] The technical solution of the present invention is: The present invention provides a method for preparing an antiferroelectric thin film, comprising the following steps: Step 1: Mixing a PbZrO3 precursor solution and an ABO3 paraelectric precursor solution according to a set ratio to obtain a mixed precursor solution; Step 2: depositing the mixed precursor solution obtained in step 1 on a substrate material, baking and pyrolyzing to obtain a first paraelectric-antiferroelectric layer, repeating the spin coating deposition, baking and pyrolysis treatment at least once, to obtain a film having at least two paraelectric-antiferroelectric layers; Step 3: Perform annealing and crystallization treatment on the film obtained in step 2 to obtain an antiferroelectric film.
[0006] Preferably, the ABO3 type compound is any one of SrTiO3, CaTiO3, CaZrO3, SrZrO3, LaScO3, LaAlO3, LaGaO3, KTaO3 and LnFeO3. Only when CaZrO3 or SrZrO3 is used as the ABO3 type compound, the antiferroelectric film contains three metal elements, and the molar ratio of metal element A to metal element B is less than 1, and the specific ratio is determined by the volume ratio of the ABO3 paraelectric precursor solution and the PbZrO3 precursor solution. The antiferroelectric films prepared using the other raw materials all contain four metal elements, and the molar ratio of metal element A to metal element B is equal to 1.
[0007] Preferably, the concentration of the PbZrO3 precursor solution is the same as that of the ABO3 paraelectric precursor solution, which is 0.1-0.4 M, and the volume ratio of the ABO3 paraelectric precursor solution to the mixed precursor solution is (1:10)-(2:3).
[0008] Preferably, in step 2, the spin coating speed is 3000-6000 rpm, and the duration is 10-60 seconds; the baking temperature is 100-500° C., and the time is 0.5-5 min; the pyrolysis temperature is 350-550° C., and the time is 0.5-5 min; In step 3, the annealing crystallization temperature is 550-800°C and the time is 3-30 minutes.
[0009] Preferably, the preparation method further includes the preparation of a lead loss prevention layer, specifically, a layer of PbO is spin-coated on the surface of each paraelectric-antiferroelectric layer or the last paraelectric-antiferroelectric layer, or when preparing the last paraelectric-antiferroelectric layer, a precursor solution containing PbO in a set proportion is added to the mixed precursor solution. Lead oxide helps prevent the loss of lead in the paraelectric-antiferroelectric layer.
[0010] Preferably, the preparation method further comprises adding 3.0% to 7.0% of bismuth nitrate or bismuth acetate to the precursor solution of step 1 in a molar percentage relative to the entire PbZrO3-ABO3 system, and controlling the pyrolysis temperature to 250 to 400°C when preparing each paraelectric-antiferroelectric layer.
[0011] The present invention also provides an antiferroelectric film, which is prepared by the above-mentioned preparation method and includes multiple paraelectric-antiferroelectric layers, each of which includes multiple paraelectric regions, and the multiple paraelectric regions are dispersed in the antiferroelectric region; wherein the paraelectric region is formed by ABO3 type compounds, and the antiferroelectric region is formed by PbZrO3.
[0012] The principle that the antiferroelectric film of the present invention can delay the antiferroelectric-ferroelectric transition field and reduce the hysteresis of the hysteresis loop is: due to the presence of paraelectric regions and antiferroelectric regions in the film, an antiferroelectric state can be formed in the antiferroelectric region, and a paraelectric state can be formed in the paraelectric region. Such a structure will break the long-range antiferroelectric order, which is an antiferroelectric regulation mechanism based on electrostatic energy, and is completed by the bound charges at the interface of the antiferroelectric / paraelectric region. Specifically, after the electric field is applied, there is an antiferroelectric-ferroelectric field-induced phase transition process in the antiferroelectric region, which will bring about a rapid increase in polarization, while the polarization of the paraelectric region is very small, which will hinder the occurrence of this field-induced phase transition, thereby delaying the antiferroelectric phase transition field. After the electric field is removed, the polarization of the paraelectric region will reversibly return to a smaller state, which will drive the antiferroelectric region to undergo a ferroelectric-antiferroelectric reverse transition in advance, thereby reducing the difference in the forward and reverse field-induced phase transitions and reducing hysteresis. The conventional regulation mechanism based on tolerance factor can improve the field-induced phase transition point, but cannot reduce hysteresis; or the conventional regulation mechanism based on relaxation antiferroelectric can reduce hysteresis but cannot improve the field-induced phase transition point. The antiferroelectric film of the present invention is an antiferroelectric regulation mechanism based on electrostatic energy, which can not only reduce hysteresis, but also improve the field-induced phase transition point.
[0013] Preferably, the dielectric constant of the ABO3 type compound is 50-200.
[0014] Preferably, the molar ratio of the metal element A to the metal element B in the paraelectric-antiferroelectric layer is ≤1.
[0015] The present invention also provides an antiferroelectric capacitor, comprising the antiferroelectric film obtained by the above preparation method, and also comprising a single crystal substrate, a conductive electrode layer and a gold electrode arranged from the inside to the outside, wherein the antiferroelectric film is located between the conductive electrode layer and the gold electrode. The present invention greatly improves the breakdown electric field and energy storage density through the use of the antiferroelectric film, and at the same time improves the relaxivity to reduce the electro-induced strain and improve the cycle performance.
[0016] Preferably, the single crystal substrate is LaAlO3, SrTiO3, Pt / Si, DyScO3, Nb-doped SrTiO3, NaCl or F-doped SnO2, In-doped SnO2, (LaAlO3) 0.3 (Sr2TaAlO6) 0.7 Any of the following: The conductive electrode layer is a LaNiO3 conductive electrode layer, a SrRuO3 conductive electrode layer, a La 0.7 Sr 0.3 Any one of the MnO3 conductive electrode layers, wherein the number of the conductive electrode layers is at least two.
[0017] The present invention also provides a method for preparing an antiferroelectric capacitor, comprising the following steps: Step A: preparing a conductive electrode layer on the surface of a single crystal substrate by spin coating technology; Step B: using the conductive electrode layer of the product obtained in step A as a substrate material, and adopting the above-mentioned preparation method to prepare an antiferroelectric thin film; Step C: Depositing a gold electrode on the surface of the antiferroelectric film through a stainless steel mask to obtain an antiferroelectric capacitor.
[0018] Preferably, in step A, the first precursor solution is deposited on the surface of the single crystal substrate by spin coating technology, and the first conductive electrode layer is obtained by baking and pyrolysis in sequence, and the spin coating deposition, baking and pyrolysis treatment are repeated at least once to obtain at least two conductive electrode layers, and then annealing crystallization treatment and aging treatment are performed to obtain the final conductive electrode layer; Wherein, the first precursor solution is LaNiO3 precursor solution, SrRuO3 precursor solution, La 0.7 Sr 0.3 Any one of the MnO3 precursor solutions.
[0019] Preferably, the baking temperature is 200-230°C, the pyrolysis temperature is 480-550°C, and the annealing crystallization temperature is 550-800°C.
[0020] The beneficial effects of the present invention are: (1) The present invention constructs a frustrated antiferroelectric structure by adding an ABO3 paraelectric precursor to the antiferroelectric material PbZrO3, and uses the polarization discontinuity of the antiferroelectric-paraelectric interface to construct an electrostatic effect, thereby achieving the effect of delaying the transition field and reducing hysteresis, and can simultaneously improve energy storage density and efficiency. In addition, the film prepared by the present invention contains several paraelectric regions and antiferroelectric regions, which can improve the antiferroelectric phase stability, increase the breakdown electric field and energy storage density, and reduce the electro-induced strain by improving the relaxivity, thereby improving the cycle performance.
[0021] (2) The present invention also adopts a variety of measures to prevent element volatilization, such as the preparation of a lead loss prevention layer, and the addition of bismuth nitrate or bismuth acetate to the mixed precursor solution. By adding bismuth nitrate or bismuth acetate to the mixed precursor solution, in addition to reducing lead loss, Bi2O3 can be formed according to the reaction, and the combustion-aiding effect of Bi2O3 can greatly reduce the temperature of the pyrolysis operation.
[0022] (3) The preparation method of the present invention is simple to operate and easy to implement. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The present invention will be further described below in conjunction with the accompanying drawings and embodiments: Figure 1The curve of the polarization intensity of the PbZrO3-LaScO3 thin film capacitor disclosed in Example 1 of the present invention as a function of the electric field, wherein a, b, c, d, and e respectively represent the curve of the polarization intensity as a function of the electric field when the volume proportion of the LaScO3 paraelectric precursor solution in the mixed precursor solution is 0-0.5; Figure 2 The curve showing the variation of the breakdown probability of the PbZrO3-LaScO3 thin film capacitor with the electric field disclosed in Example 1 of the present invention; Figure 3 The curve of energy storage density and energy storage efficiency of the PbZrO3-LaScO3 thin film capacitor disclosed in Example 1 of the present invention as a function of the electric field; Figure 4 The curve showing the change of energy storage density and energy storage efficiency of the PbZrO3-LaScO3 film capacitor with the number of cycles disclosed in Example 1 of the present invention; Figure 5 It is the distribution diagram of the paraelectric region and the antiferroelectric region in the paraelectric-antiferroelectric layer, where e1 represents the antiferroelectric region and e2 represents the paraelectric region. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with specific embodiments and with reference to the accompanying drawings. It should be understood that these descriptions are only exemplary and are not intended to limit the scope of the present invention. In addition, in the following description, the description of well-known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.
[0025] The embodiment of the present invention discloses an antiferroelectric thin film and a method for preparing the same: Step 1. Mix the PbZrO3 precursor solution and the ABO3 paraelectric precursor solution in a set ratio to obtain a mixed precursor solution; the ABO3 type compound includes any one of SrTiO3, CaTiO3, CaZrO3, SrZrO3, LaScO3, LaAlO3, LaGaO3, KTaO3 and LnFeO3, the concentration of the PbZrO3 precursor solution is the same as that of the ABO3 paraelectric precursor solution, and the volume ratio of the added amount of the ABO3 paraelectric precursor solution to the mixed precursor solution is (1:10)~(2:3). Specifically, it is necessary to control the ABO3 paraelectric precursor solution not to exceed 2 / 3 of the total volume of the mixed precursor solution, and not less than 1 / 10 of the total volume of the mixed liquid precursor.
[0026] The preparation process of the PbZrO3 precursor solution is as follows: lead acetate is dissolved in a solvent and heated at 60-150°C for 0.5-3 hours; after cooling to room temperature, zirconium n-propoxide is introduced into the solution, and the obtained mixed solution is continuously stirred for 1-3 hours under ambient conditions to ensure that the zirconium n-propoxide is completely dissolved, thereby obtaining a clear and transparent PbZrO3 precursor solution with a concentration of 0.1-0.4M; The preparation process of ABO3 paraelectric precursor solution is as follows: taking the preparation of SrTiO3, LaScO3, and CaTiO3 as an example, equal amounts of metal A source and metal B source (strontium acetate and tetrabutyl titanate, lanthanum nitrate and scandium nitrate, or calcium acetate and tetrabutyl titanate) are dissolved in a solvent at a temperature of 60~150°C for 0.5~3 hours, and the obtained mixture is continuously stirred for 1~3 hours until it is completely dissolved to obtain an ABO3 paraelectric precursor solution (SrTiO3 precursor solution, LaScO3 precursor solution or CaTiO3 precursor solution) with a concentration of 0.1~0.4M. The solvent used to prepare the precursor solution is one or more of 2-methoxyethanol, propionic acid, ethylene glycol, and acetic acid. In addition to nitrates, soluble acetates or chlorides can also be used for the metal A source and metal B source of the precursor solution.
[0027] Step 2: spin-coat the mixed precursor solution obtained in step 1 onto a substrate material, and obtain a first paraelectric-antiferroelectric layer by baking and pyrolysis. Repeat the spin-coating, baking and pyrolysis treatments at least once to obtain a film having at least two paraelectric-antiferroelectric layers. The thickness of the film can be determined according to user needs. For example, when an antiferroelectric film is used to prepare a capacitor, the thickness of the film can be selected to be 100~1000nm.
[0028] Among them, the spin coating speed is 3000~6000 rpm, and the duration is 10~60 seconds; the baking temperature is 100~500℃, and the time is 0.5~5min to promote the evaporation of the solvent; the pyrolysis temperature is 350~550℃, and the time is 0.5~5min to eliminate residual organic matter; further preferably, the baking temperature is 200~230℃, and the pyrolysis temperature is 480~550℃.
[0029] Step 3: performing annealing and crystallization treatment on the film obtained in step 2 to obtain an antiferroelectric film.
[0030] Among them, the annealing crystallization temperature is 550~800℃, and the time is 3~30min.
[0031] In some improved embodiments, bismuth nitrate or bismuth acetate may be added to the mixed precursor solution at a molar percentage of 3.0% to 7.0% relative to the entire PbZrO3-ABO3 system. At the same time, when each paraelectric-antiferroelectric layer is prepared by spin coating deposition, the pyrolysis temperature is controlled to be 250 to 400°C. By adding bismuth nitrate or bismuth acetate to the mixed precursor solution, Bi2O3 can be formed, which has a sintering effect and can reduce the temperature of the pyrolysis treatment by about 100°C, from 350 to 500°C to 250 to 400°C. On the one hand, the effect of Pb volatilization loss can be reduced due to the reduction of the pyrolysis temperature, and on the other hand, energy consumption can be reduced to reduce costs.
[0032] In some improved embodiments, a layer of PbO can be spin-coated on the surface of each paraelectric-antiferroelectric layer or the last paraelectric-antiferroelectric layer; specifically, a layer of PbO oxide can be deposited on each paraelectric-antiferroelectric layer, and PbO oxide can be deposited on the last paraelectric-antiferroelectric layer, which helps prevent the loss of volatile metal element Pb in the antiferroelectric film. In addition, when preparing the last paraelectric-antiferroelectric layer, a PbO precursor solution can be added to the mixed precursor solution to simplify the process and improve the preparation efficiency. Taking the PbO precursor solution as an example, the preparation process is: dissolve lead acetate in a solvent, heat at 60~150℃ for 1~3 hours, and obtain a PbO precursor solution with a concentration of 0.1~0.4M.
[0033] The antiferroelectric film comprises a plurality of paraelectric-antiferroelectric layers, each of which comprises a plurality of paraelectric regions, wherein the plurality of paraelectric regions are dispersedly distributed in the antiferroelectric region, wherein the paraelectric region is formed by an ABO3 type compound, the antiferroelectric region is formed by PbZrO3, and the molar ratio of metal element A to metal element B in the paraelectric-antiferroelectric layer is ≤ 1. In order to prevent the loss of lead in the paraelectric-antiferroelectric layer, a layer of lead oxide may be provided on the surface of each paraelectric-antiferroelectric layer or the last paraelectric-antiferroelectric layer in the plurality of paraelectric-antiferroelectric layers.
[0034] The embodiment of the present invention further discloses a high energy storage density antiferroelectric capacitor and a preparation method thereof, wherein the antiferroelectric thin film of the antiferroelectric capacitor is provided with a lead loss prevention layer: Step A, depositing the first precursor solution on the surface of the single crystal substrate by spin coating technology, baking and pyrolysis in sequence to obtain a first conductive electrode layer, repeating the spin coating deposition, baking and pyrolysis treatments at least once to obtain at least two conductive electrode layers, and then performing annealing crystallization treatments and aging treatments to obtain the final conductive electrode layer; the present invention can reduce the resistivity of the conductive electrode layer through multiple spin coating deposition treatments.
[0035] Among them, the single crystal substrate is LaAlO3, SrTiO3, Pt / Si, DyScO3, Nb-doped SrTiO3, NaCl or F-doped SnO2, In-doped SnO2, (LaAlO3) 0.3 (Sr2TaAlO6) 0.7 Any of the following: The first precursor solution includes LaNiO3 precursor solution, SrRuO3, La 0.7 Sr 0.3 Any one of MnO3; the preparation process of the first precursor solution (taking LaNiO3 as an example) is: at 25-100°C, lanthanum nitrate and nickel acetate are dissolved in a solvent at a molar ratio of 1:1 for 5-30 minutes, and stirred continuously at room temperature for 1-6 hours to obtain a clear and transparent LaNiO3 precursor solution with a concentration of 0.1-0.4M, wherein the solvent used is one or more of 2-methoxyethanol, propionic acid, ethylene glycol, and acetic acid, and the solvent can be completely removed during pyrolysis and annealing crystallization treatment; The spin coating speed is 3000-6000 rpm, and the duration is 10-60 seconds; the baking temperature is 100-500°C, and the time is 0.5-5 minutes to promote the evaporation of the solvent; the pyrolysis temperature is 350-550°C, and the time is 0.5-5 minutes to eliminate the residual organic matter; the annealing crystallization temperature is 550-800°C, and the time is 3-30 minutes; the aging treatment time is 48 hours. More preferably, the baking temperature is 200-230°C, the pyrolysis temperature is 480-550°C, and the annealing crystallization temperature is 550-800°C.
[0036] Step B, mixing the PbZrO3 precursor solution and the ABO3 paraelectric precursor solution in a set ratio to obtain a mixed precursor solution, spin-coating and depositing the mixed precursor solution on the surface of the conductive electrode layer to obtain an antiferroelectric film having multiple paraelectric-antiferroelectric layers, and depositing the PbO precursor solution on the surface of the antiferroelectric film by spin coating technology to obtain a lead loss prevention layer.
[0037] The dielectric constant of the ABO3 type compound is 50 to 200. The preparation of the antiferroelectric thin film of the paraelectric-antiferroelectric layer is specifically referred to the above-mentioned method for preparing the antiferroelectric thin film.
[0038] Step C: depositing a gold electrode on the surface of the lead loss prevention layer through a stainless steel mask to obtain an antiferroelectric capacitor with high energy storage density.
[0039] The antiferroelectric capacitor comprises a single crystal substrate, a conductive electrode layer and a gold electrode arranged from the inside to the outside, an antiferroelectric film is arranged between the conductive electrode layer and the gold electrode, and a lead loss prevention layer is arranged on the surface of the antiferroelectric film.
[0040] The invention selects the spin coating deposition method to prepare the antiferroelectric film and the high energy storage density antiferroelectric capacitor, the purpose of which is to use the film layer as a conductive electrode on the one hand, and on the other hand, the transition buffer layer makes the antiferroelectric film and the single crystal substrate more compatible.
[0041] Example 1 This embodiment provides an antiferroelectric capacitor containing a PbZrO3-LaScO3 antiferroelectric film and a preparation method thereof, wherein the preparation method comprises the following steps: Step A: Using LaAlO3 as a single crystal substrate, prepare a LaNiO3 conductive electrode layer on the LaAlO3 substrate (1) Preparation of LaNiO3 precursor solution: Lanthanum nitrate and nickel acetate were dissolved in a solvent (2-methoxyethanol: propionic acid in a volume ratio of 1:1) at 70°C for 30 minutes and stirred at room temperature for 5 hours to obtain a clear and transparent LaNiO3 precursor solution with a concentration of 0.3 M.
[0042] (2) Preparation of LaNiO3 conductive electrode layer: LaAlO3 was used as a single crystal substrate, and the LaNiO3 precursor solution was deposited on the surface of the single crystal substrate by spin coating technology. The spin coating speed was 6000 rpm and the duration was 30 seconds. The first conductive electrode layer was obtained by baking and pyrolysis in sequence. The baking temperature was 250°C and the time was 2.5 minutes each time. The pyrolysis temperature was 400°C and the time was 5 minutes each time. The spin coating deposition, baking and pyrolysis treatments were then repeated to obtain two conductive electrode layers. Annealing crystallization treatment and aging treatment were performed to obtain the final conductive electrode layer. The annealing crystallization temperature was 680°C and the time was 15 minutes. The aging treatment time was 48 hours.
[0043] Step B: Preparation of PbZrO3-LaScO3 antiferroelectric thin film (1) Preparation of mixed precursor solution Lead acetate was dissolved in a solvent (2-methoxyethanol, ethylene glycol, acetic acid in a volume ratio of 1:1:1) and heated at 85°C for 2 hours. After cooling to room temperature, zirconium n-propoxide was introduced into the solution, and the resulting mixture was stirred continuously for 2 hours under ambient conditions to ensure that the zirconium n-propoxide was completely dissolved, thereby obtaining a clear and transparent PbZrO3 precursor solution with a concentration of 0.3M.
[0044] Lanthanum nitrate and scandium nitrate in a molar ratio of 1:1 were dissolved in a solvent (2-methoxyethanol, ethylene glycol, and acetic acid in a volume ratio of 1:1:1) at 85°C for 1 hour, and the resulting mixture was stirred for 3 hours until it was completely dissolved to obtain a LaScO3 paraelectric precursor solution with a concentration of 0.3M.
[0045] The PbZrO3 precursor solution and the LaScO3 paraelectric precursor solution are mixed in a set ratio to obtain a mixed precursor solution, and the ratio of the volume of the LaScO3 paraelectric precursor solution to the volume of the mixed precursor solution is 0, 0.1, 0.2, 0.3, and 0.5, respectively.
[0046] (2) Spin coating the mixed precursor solution onto the conductive electrode layer prepared in step A at a speed of 6000 rpm for 30 seconds; then, the first paraelectric-antiferroelectric layer is obtained by baking and pyrolysis, and the spin coating, baking and pyrolysis treatments are repeated 9 times to obtain a thin film having ten paraelectric-antiferroelectric layers, wherein the baking temperature is 200°C for 2 minutes each time to promote the evaporation of the solvent, and the pyrolysis temperature is 400°C for 5 minutes each time to eliminate residual organic matter.
[0047] (3) Preparation of PbO layer Lead acetate was dissolved in a solvent (2-methoxyethanol, ethylene glycol, and acetic acid in a volume ratio of 1:1:1), heated at 85°C for 2 hours, and stirred at room temperature for 2 hours to obtain a clear and transparent PbO precursor solution with a concentration of 0.3 M.
[0048] The PbO precursor solution is spin-coated on the paraelectric-antiferroelectric film prepared in step B (2) at a spin-coating speed of 6000 rpm for 30 seconds; and then the anti-volatile layer is obtained by baking and pyrolysis. The baking temperature is 200°C for 2 minutes each time to promote the evaporation of the solvent, and the pyrolysis temperature is 400°C for 5 minutes each time to eliminate the residual organic matter.
[0049] (4) The thin film obtained in step (3) is subjected to annealing and crystallization treatment to obtain an antiferroelectric thin film, wherein the annealing and crystallization temperature is 700° C. and the time is 15 minutes.
[0050] Step C: Then, a gold electrode is deposited on the surface of the lead loss prevention layer through a stainless steel mask to obtain an antiferroelectric capacitor with high energy storage density.
[0051] In this embodiment, a thin film capacitor is obtained by depositing a gold electrode onto the surface of the PbO lead loss prevention layer through a stainless steel mask, and the hysteresis loop, breakdown field strength, energy storage density and efficiency, and cycle stability of the prepared PbZrO3-LaScO3 thin film capacitor are tested. In which, in the mixed precursor solution for preparing the PbZrO3-LaScO3 antiferroelectric thin film, the volume ratio of the paraelectric precursor solution LaScO3 precursor solution is defined as x. At this time, the volume ratio of the PbZrO3 precursor solution is 1-x, and the value of x is 0, 0.1, 0.2, 0.3, and 0.5.
[0052] Figure 1The curve of the change of polarization intensity of PbZrO3-LaScO3 film capacitor with electric field shows the hysteresis loop measured under different electric fields (until the breakdown electric field). Figure 1 It can be seen that the volume proportion of the paraelectric precursor solution LaScO3 in the mixed precursor solution x = 0.2, the hysteresis loop of the prepared PbZrO3-LaScO3 film capacitor has a higher phase transition electric field (~1 MV cm -1 ) and smaller hysteresis.
[0053] Figure 2 The breakdown probability of the PbZrO3-LaScO3 film capacitor varies with the electric field. The horizontal axis is the electric field and the vertical axis is the breakdown probability. Figure 2 It can be seen that the volume proportion of the paraelectric precursor solution LaScO3 in the mixed precursor solution x = 0.2, the prepared PbZrO3-LaScO3 film capacitor has a higher breakdown electric field.
[0054] Figure 3 The energy storage density and energy storage efficiency of the PbZrO3-LaScO3 film capacitor vary with the electric field. The horizontal axis in the figure is the electric field, the vertical axis on the left is the energy storage density, and the vertical axis on the right is the energy storage efficiency. The upper part of the figure is the curve of the energy storage efficiency varying with the electric field, and the lower part is the curve of the energy storage density varying with the electric field. Figure 3 It can be seen that after adding the paraelectric precursor solution LaScO3 to the mixed precursor solution, the prepared PbZrO3-LaScO3 film capacitor can achieve up to 190 J / cm 3 energy storage density and efficiency >80%.
[0055] Figure 4 The curves of energy storage density and energy storage efficiency of PbZrO3-LaScO3 film capacitors changing with the number of cycles show the cycle stability of PbZrO3-LaScO3 film capacitors. In the figure, the horizontal axis represents the number of cycles, the left vertical axis represents the energy storage density, and the right vertical axis represents the energy storage efficiency. The upper part of the figure shows the curve of energy storage efficiency changing with the number of cycles, and the lower part shows the curve of energy storage density changing with the number of cycles. Figure 4 It can be seen from the figure that after adding the paraelectric precursor solution LaScO3 into the mixed precursor solution, the energy storage density of the prepared PbZrO3-LaScO3 film capacitor can reach 10 7 After the cycle, it can remain basically unchanged.
[0056] Figure 5 is the distribution diagram of the paraelectric region and the antiferroelectric region in the paraelectric-antiferroelectric layer, where e1 represents the antiferroelectric region and e2 represents the paraelectric region. Figure 5 As shown, a plurality of the paraelectric regions are dispersed in the antiferroelectric region.
[0057] Example 2 This embodiment provides an antiferroelectric capacitor containing a PbZrO3-CaZrO3 antiferroelectric thin film and a preparation method thereof, wherein the preparation method comprises the following steps: Step A: Using LaAlO3 as a single crystal substrate, prepare a LaNiO3 conductive electrode layer on the LaAlO3 substrate (1) Preparation of LaNiO3 precursor solution: Lanthanum nitrate and nickel acetate were dissolved in a solvent (2-methoxyethanol: propionic acid in a volume ratio of 1:1) at 70°C for 30 minutes and stirred at room temperature for 5 hours to obtain a clear and transparent LaNiO3 precursor solution with a concentration of 0.3 M.
[0058] (2) Preparation of LaNiO3 conductive electrode layer: LaAlO3 was used as a single crystal substrate, and the LaNiO3 precursor solution was deposited on the surface of the single crystal substrate by spin coating technology. The spin coating speed was 6000 rpm and the duration was 30 seconds. The first conductive electrode layer was obtained by baking and pyrolysis in sequence. The baking temperature was 250°C and the time was 2.5 minutes each time. The pyrolysis temperature was 400°C and the time was 5 minutes each time. The spin coating deposition, baking and pyrolysis treatments were then repeated to obtain two conductive electrode layers. Annealing crystallization treatment and aging treatment were performed to obtain the final conductive electrode layer. The annealing crystallization temperature was 680°C and the time was 15 minutes. The aging treatment time was 48 hours.
[0059] Step B: Preparation of PbZrO3-CaZrO3 antiferroelectric thin film (1) Preparation of mixed precursor solution Lead acetate was dissolved in a solvent (2-methoxyethanol, ethylene glycol, acetic acid in a volume ratio of 1:1:1) and heated at 85°C for 2 hours. After cooling to room temperature, zirconium n-propoxide was introduced into the solution, and the resulting mixture was stirred continuously for 2 hours under ambient conditions to ensure that the zirconium n-propoxide was completely dissolved, thereby obtaining a clear and transparent PbZrO3 precursor solution with a concentration of 0.3M.
[0060] Calcium acetate was dissolved in a solvent (2-methoxyethanol, ethylene glycol, and acetic acid in a volume ratio of 1:1:1) and heated at 85°C for 2 hours. After cooling to room temperature, zirconium n-propoxide was introduced into the solution, and the resulting mixture was continuously stirred for 2 hours under ambient conditions to ensure that the zirconium n-propoxide was completely dissolved, thereby obtaining a clear and transparent CaZrO3 precursor solution with a concentration of 0.3M.
[0061] The PbZrO3 precursor solution and the CaZrO3 paraelectric precursor solution are mixed in a set ratio to obtain a mixed precursor solution, and the ratio of the volume of the CaZrO3 paraelectric precursor solution to the volume of the mixed precursor solution is 0.1 and 0.2.
[0062] (2) Spin coating the mixed precursor solution onto the conductive electrode layer prepared in step A at a speed of 6000 rpm for 30 seconds; then, the first paraelectric-antiferroelectric layer is obtained by baking and pyrolysis. The spin coating, baking and pyrolysis treatments are repeated 9 times to obtain a thin film having ten paraelectric-antiferroelectric layers, wherein the baking temperature is 200°C for 2 minutes each time to promote the evaporation of the solvent, and the pyrolysis temperature is 400°C for 5 minutes each time to eliminate residual organic matter.
[0063] (3) Preparation of PbO layer Lead acetate was dissolved in a solvent (2-methoxyethanol, ethylene glycol, and acetic acid in a volume ratio of 1:1:1), heated at 85°C for 2 hours, and stirred at room temperature for 2 hours to obtain a clear and transparent PbO precursor solution with a concentration of 0.3 M.
[0064] The PbO precursor solution is spin-coated on the paraelectric-antiferroelectric film prepared in step B (2) at a spin-coating speed of 6000 rpm for 30 seconds; and then the anti-volatile layer is obtained by baking and pyrolysis. The baking temperature is 200°C for 2 minutes each time to promote the evaporation of the solvent, and the pyrolysis temperature is 400°C for 5 minutes each time to eliminate the residual organic matter.
[0065] (4) The thin film obtained in step (3) is subjected to annealing and crystallization treatment to obtain an antiferroelectric thin film, wherein the annealing and crystallization temperature is 700° C. and the time is 15 minutes.
[0066] Step C: Then, a gold electrode is deposited on the surface of the lead loss prevention layer through a stainless steel mask to obtain an antiferroelectric capacitor with high energy storage density.
[0067] The energy storage density and efficiency of the antiferroelectric capacitor prepared in this embodiment under the breakdown electric field are shown in Table 1 below: Table 1
[0068] Example 3 This embodiment provides an antiferroelectric capacitor containing a PbZrO3-CaZrO3 antiferroelectric thin film and a preparation method thereof, wherein the preparation method comprises the following steps: Step A: Using LaAlO3 as a single crystal substrate, prepare a LaNiO3 conductive electrode layer on the LaAlO3 substrate (1) Preparation of LaNiO3 precursor solution: Lanthanum nitrate and nickel acetate were dissolved in a solvent (2-methoxyethanol: propionic acid in a volume ratio of 1:1) at 70°C for 30 minutes and stirred at room temperature for 5 hours to obtain a clear and transparent LaNiO3 precursor solution with a concentration of 0.3 M.
[0069] (2) Preparation of LaNiO3 conductive electrode layer: LaAlO3 was used as a single crystal substrate, and the LaNiO3 precursor solution was deposited on the surface of the single crystal substrate by spin coating technology. The spin coating speed was 6000 rpm and the duration was 30 seconds. The first conductive electrode layer was obtained by baking and pyrolysis in sequence. The baking temperature was 250°C and the time was 2.5 minutes each time. The pyrolysis temperature was 400°C and the time was 5 minutes each time. The spin coating deposition, baking and pyrolysis treatments were then repeated to obtain two conductive electrode layers. Annealing crystallization treatment and aging treatment were performed to obtain the final conductive electrode layer. The annealing crystallization temperature was 680°C and the time was 15 minutes. The aging treatment time was 48 hours.
[0070] Step B: Preparation of PbZrO3-CaZrO3 antiferroelectric thin film (1) Preparation of mixed precursor solution Lead acetate was dissolved in a solvent (2-methoxyethanol, ethylene glycol, acetic acid in a volume ratio of 1:1:1) and heated at 85°C for 2 hours. After cooling to room temperature, zirconium n-propoxide was introduced into the solution, and the resulting mixture was stirred continuously for 2 hours under ambient conditions to ensure that the zirconium n-propoxide was completely dissolved, thereby obtaining a clear and transparent PbZrO3 precursor solution with a concentration of 0.3M.
[0071] Calcium acetate was dissolved in a solvent (2-methoxyethanol, ethylene glycol, and acetic acid in a volume ratio of 1:1:1) and heated at 85°C for 2 hours. After cooling to room temperature, zirconium n-propoxide was introduced into the solution, and the resulting mixture was continuously stirred for 2 hours under ambient conditions to ensure that the zirconium n-propoxide was completely dissolved, thereby obtaining a clear and transparent CaZrO3 precursor solution with a concentration of 0.3M.
[0072] The PbZrO3 precursor solution and the CaZrO3 paraelectric precursor solution are mixed in a volume ratio of 4:1 to obtain a mixed precursor solution, wherein the ratio of the volume of the CaZrO3 paraelectric precursor solution to the volume of the mixed precursor solution is 0.2; then 4.0% of bismuth nitrate in molar percentage relative to the entire PbZrO3-CaZrO3 system is added to the above mixed precursor solution, and the mixture is mixed and stirred evenly.
[0073] (2) Spin coating the mixed precursor solution with bismuth nitrate added onto the conductive electrode layer prepared in step A at a speed of 6000 rpm for 30 seconds; then, the first paraelectric-antiferroelectric layer is obtained by baking and pyrolysis. The spin coating, baking and pyrolysis treatments are repeated 9 times to obtain a thin film having ten paraelectric-antiferroelectric layers, wherein the baking temperature is 200°C for 2 minutes each time to promote the evaporation of the solvent, and the pyrolysis temperature is 400°C for 5 minutes each time to eliminate residual organic matter.
[0074] (3) Preparation of PbO layer Lead acetate was dissolved in a solvent (2-methoxyethanol, ethylene glycol, and acetic acid in a volume ratio of 1:1:1), heated at 85°C for 2 hours, and stirred at room temperature for 2 hours to obtain a clear and transparent PbO precursor solution with a concentration of 0.3 M.
[0075] The PbO precursor solution is spin-coated on the paraelectric-antiferroelectric film prepared in step B (2) at a spin-coating speed of 6000 rpm for 30 seconds; and then the anti-volatile layer is obtained by baking and pyrolysis. The baking temperature is 200°C for 2 minutes each time to promote the evaporation of the solvent, and the pyrolysis temperature is 400°C for 5 minutes each time to eliminate the residual organic matter.
[0076] (4) The thin film obtained in step (3) is subjected to annealing and crystallization treatment to obtain an antiferroelectric thin film, wherein the annealing and crystallization temperature is 670° C. and the time is 15 minutes.
[0077] Step C: Then, a gold electrode is deposited on the surface of the lead loss prevention layer through a stainless steel mask to obtain an antiferroelectric capacitor with high energy storage density.
[0078] The energy storage density and efficiency of the antiferroelectric capacitor prepared in this embodiment under the breakdown electric field are shown in Table 2 below: Table 2
[0079] It should be understood that the above specific embodiments of the present invention are only used to illustrate or explain the principles of the present invention, and do not constitute a limitation of the present invention. Therefore, any modifications, equivalent substitutions, improvements, etc. made without departing from the spirit and scope of the present invention should be included in the protection scope of the present invention. In addition, the appended claims of the present invention are intended to cover all changes and modifications that fall within the scope and boundaries of the appended claims, or the equivalent forms of such scope and boundaries.
Claims
1. A method for preparing an antiferroelectric thin film, characterized in that: The following steps are involved: Step 1: Mixing a PbZrO3 precursor solution and an ABO3 paraelectric precursor solution according to a set ratio to obtain a mixed precursor solution; Step 2: depositing the mixed precursor solution obtained in step 1 on a substrate material, baking and pyrolyzing to obtain a first paraelectric-antiferroelectric layer, repeating the spin coating deposition, baking and pyrolysis treatment at least once, to obtain a film having at least two paraelectric-antiferroelectric layers; Step 3: Perform annealing and crystallization treatment on the film obtained in step 2 to obtain an antiferroelectric film.
2. The preparation method according to claim 1, characterized in that: The ABO3 type compound is any one of SrTiO3, CaTiO3, CaZrO3, SrZrO3, LaScO3, LaAlO3, LaGaO3, KTaO3 and LnFeO3.
3. The preparation method according to claim 1, characterized in that: The concentration of the PbZrO3 precursor solution is the same as that of the ABO3 paraelectric precursor solution, which is 0.1-0.4M, and the volume ratio of the ABO3 paraelectric precursor solution to the mixed precursor solution is (1:10)-(2:3).
4. The preparation method according to claim 1, characterized in that: In step 2, the spin coating speed is 3000-6000 rpm, and the duration is 10-60 seconds; the baking temperature is 100-500° C., and the time is 0.5-5 min; the pyrolysis temperature is 350-550° C., and the time is 0.5-5 min; In step 3, the annealing crystallization temperature is 550-800°C and the time is 3-30 minutes.
5. The preparation method according to claim 1, characterized in that: The preparation method also includes the preparation of a lead loss prevention layer, and the specific method is: spin coating and depositing a layer of PbO on the surface of each paraelectric-antiferroelectric layer or the last paraelectric-antiferroelectric layer, or when preparing the last paraelectric-antiferroelectric layer, adding a set proportion of a precursor solution containing PbO to the mixed precursor solution.
6. The preparation method according to claim 1, characterized in that: The preparation method also includes adding 3.0% to 7.0% of bismuth nitrate or bismuth acetate in molar percentage relative to the entire PbZrO3-ABO3 system to the precursor solution in step 1, and controlling the pyrolysis temperature to 250 to 400°C when preparing each paraelectric-antiferroelectric layer.
7. An antiferroelectric thin film, characterized in that: It is prepared by the preparation method described in any one of claims 1 to 6, comprising multiple paraelectric-antiferroelectric layers, each of the paraelectric-antiferroelectric layers comprising multiple paraelectric regions, and the multiple paraelectric regions are dispersed in the antiferroelectric region; wherein the paraelectric region is formed by an ABO3 type compound, and the antiferroelectric region is formed by PbZrO3.
8. An antiferroelectric capacitor, characterized in that: The invention comprises an antiferroelectric film obtained by the preparation method according to any one of claims 1 to 6, and also comprises a single crystal substrate, a conductive electrode layer and a gold electrode arranged from the inside to the outside, wherein the antiferroelectric film is located between the conductive electrode layer and the gold electrode.
9. The antiferroelectric capacitor according to claim 8, characterized in that: The single crystal substrate is LaAlO3, SrTiO3, Pt / Si, DyScO3, Nb-doped SrTiO3, NaCl or F-doped SnO2, In-doped SnO2, (LaAlO3) 0.3 (Sr2TaAlO6) 0.7 Any of the following: The conductive electrode layer is a LaNiO3 conductive electrode layer, a SrRuO3 conductive electrode layer, a La 0.7 Sr 0.3 Any one of the MnO3 conductive electrode layers, wherein the number of the conductive electrode layers is at least two.
10. A method for preparing an antiferroelectric capacitor, characterized in that: The following steps are involved: Step A: preparing a conductive electrode layer on the surface of a single crystal substrate by spin coating technology; Step B: using the conductive electrode layer of the product obtained in step A as a substrate material, and preparing an antiferroelectric thin film by the preparation method described in any one of claims 1 to 6; Step C: Depositing a gold electrode on the surface of the antiferroelectric film through a stainless steel mask to obtain an antiferroelectric capacitor.
11. The preparation method according to claim 10, characterized in that: In step A, a first precursor solution is deposited on the surface of a single crystal substrate by spin coating technology, and a first conductive electrode layer is obtained by baking and pyrolysis in sequence, and the spin coating deposition, baking and pyrolysis treatments are repeated at least once to obtain at least two conductive electrode layers, and then annealing crystallization treatment and aging treatment are performed to obtain a final conductive electrode layer; Wherein, the first precursor solution is LaNiO3 precursor solution, SrRuO3 precursor solution, La 0.7 Sr 0.3 Any one of the MnO3 precursor solutions.
Citation Information
Patent Citations
Anti-ferroelectric-paraelectric material coupled capacitor dielectric and preparation method therefor
CN106531442A
Integrated circuit device
CN117641935A
Anti-ferroelectric material, preparation method thereof and thin film capacitor
CN117986016A
Capacitor, electric circuit, circuit board, electronic apparatus, and power storage device
US20240038450A1